Discussion about math, puzzles, games and fun. Useful symbols: ÷ × ½ √ ∞ ≠ ≤ ≥ ≈ ⇒ ± ∈ Δ θ ∴ ∑ ∫ π -¹ ² ³ °

You are not logged in.

- Topics: Active | Unanswered

**the_white_sheep****Member**- Registered: 2005-09-05
- Posts: 9

Hi

I know this may look easy for some people but I'm just grasping it. Please look at the following simultaneous equation and see what you get. Thanks alot.

Please show me the easiest way to work this out so that I can apply it to other questions.

3p + 2q = 9

4p - 6q = 25

Please let me know how you worked it out as well.

Thanks

Hozan

Offline

**mathsyperson****Moderator**- Registered: 2005-06-22
- Posts: 4,900

We need to make one of the terms in one the equations equivalent to one of the terms in the other equation.

The easiest way to do this would be to multiply everything in the first equation by 3:

9p + 6q = 27

4p - 6q = 25

Adding these equations together cancels the 'q' terms, so we are left with 13p = 52 which gives p = 4.

Substitute p = 4 into one of the equations: (3x4) + 2q = 9

12 + 2q = 9

2q = -3

q = -1.5

Check with the other: (4x4) - (6x-1.5) = 25

As that equation is meant to equal 25, that means that I got it right.

Why did the vector cross the road?

It wanted to be normal.

Offline

**the_white_sheep****Member**- Registered: 2005-09-05
- Posts: 9

thanks alot, great job

Offline